Study on Hydraulic Fracture Propagation of Strong Heterogeneous Shale Based on Stress‐Seepage Damage Coupling Model - Wei Liu; Lei Xiao; Yunbin Ke; Yang Zhi; Kangxing Dong (Energy Science & Engineering)
ABSTRACT The developed laminar structure of shale makes it possess obvious anisotropic characteristics, and these anisotropic characteristics are one of the important factors leading to the strong and weak heterogeneous properties of shale. Additionally, there is a common phenomenon where the propagation of hydraulic fracture heights is limited in the hydraulic fracturing process of strongly heterogeneous shale reservoirs. To clarify the reasons for the limited height propagation of hydraulic fractures in strongly heterogeneous shale reservoirs, numerical simulation methods were used to study the propagation patterns of hydraulic fractures in shale reservoirs under different levels of anisotropy, flow rate, viscosity, and stress differences. The results show that as the anisotropy value increases and the heterogeneity becomes stronger, it becomes more difficult for hydraulic fractures to expand along the fracture height direction, and the fracture width at the fracture opening becomes larger. For strongly heterogeneous shale reservoir, the hydraulic fracture height can be increased within a certain range by increasing the flow rate, viscosity, and stress difference. When the upper limit value is exceeded, the hydraulic fracture height of the strong heterogeneous shale reservoir gradually becomes stable, and the increasing trend is no longer obvious. The strong or weak heterogeneity caused by the inherent anisotropic characteristics of shale reservoirs affects the development and transformation effectiveness of shale reservoirs. The research in this article will provide some reference material and guidance for the efficient development of shale reservoirs.